HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DENGAN KEMAMPUAN PUKULAN FOREHAND OVERHEAD LOB DALAM PERMAINAN BULUTANGKIS PB. RUMBIO JAYA - Rifaldi Ardi; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The study aims to identify how the flexibility of the wrist with ability of a stroke forehand overhead lob in the game of badminton PB.Rumbio Jaya.the population in this study is a badminton PB.Rumbio Jaya, population in this research is 8 people consisting of the men, By using techniques total sampling the entire population made in the sample.based on variable in this study then the research used is variables are the flexibility of the wrist to use tools to measure the degree and variables are the ability of a lob.data to be a test of normality with a lilifors the first significan α = 0.05 .based on the results of research has been outlined in chapters earlier can be taken in that there is a significant connection be tween the flexibility of the wrist(X) with ability of a lob(Y) athlete Badminton PB.Rumbio Jaya provided rcount=0.957 > rtab=0.754Keyword: Wrist Flexibility, Ability Of A Lob